Benign non-immune cells in tumor microenvironment - Liu, Shaowen; Liu, Chunhui; He, Yuan; Li, Jun (Frontiers in Immunology, 2025)
The tumor microenvironment (TME) is a highly complex and continuous evolving ecosystem, consisting of a diverse array of cellular and non-cellular components. Among these, benign non-immune cells, including cancer-associated fibroblasts (CAFs), adipocytes, endothelial cells (ECs), pericytes (PCs), Schwann cells (SCs) and others, are crucial factors for tumor development. Benign non-immune cells within the TME interact with both tumor cells and immune cells. These interactions contribute to tumor progression through both direct contact and indirect communication. Numerous studies have highlighted the role that benign non-immune cells exert on tumor progression and potential tumor-promoting mechanisms via multiple signaling pathways and factors. However, these benign non-immune cells may play different roles across cancer types. Therefore, it is important to understand the potential roles of benign non-immune cells within the TME based on tumor heterogeneity. A deep understanding allows us to develop novel cancer therapies by targeting these cells. In this review, we will introduce several types of benign non-immune cells that exert on different cancer types according to tumor heterogeneity and their roles in the TME.